RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ABILITY OF DEVELOPING PARAGRAPH WITH ABILITY OF ARGUMENTATIVE WRITING OF THE STUDENTS CLASS VIII SMP NEGERI 1 TOMIA - Liamawarti Liamawarti (Universitas Sembilanbelas November Kolaka, 2016)
The purpose of the research is aimed to investigate is there 1) relationship between emotional intelligence and writing argumentation ability; 2) relationship between paragraph development and writing argumentation ability; 3) relationship between emotional intelligence and paragraph development and writing argumentation of students at grade VIII SMP Negeri 1 Tomia. This research employs survey method with correlation approach. The population of the research is 103 people. The sample is 51 students which taken with simple random sampling. The data is collected by using instrument which was empirically tested to find out the validity and reliability. Result of the research find that: (1) there is a significant between emotional intelligence and writing argumentation ability showing with the correlation coefficient (ry1) 0,554 with sig. 0.000 ≤ 0.05; (2) there is a significant relationship between developing paragraph and writing argumentation ability showing with the correlation coefficient (ry2) 0,619 sig 0.00 ≤ 0.05; and (3) there is a significant relationship between emotional intelligence and paragraph developing with writing argumentation ability showing with correlation coefficient (ry1.2) 0,703 sig. 0.000 ≤ 0.05. From these findings, it can be concluded that there is a significant relationship between emotional intelligence and writing argumentation ability, developing paragraph and writing argumentation ability of students class VII SMP Negeri 1 Tomia.